A survey and analysis of multiphase electric propulsion motors and associated controllers for driving underwater platforms - Arun Singh; Anita Khosla (Propulsion and Power Research, 2025)
Propulsion motors are essential for driving underwater platforms, which are designed to explore and exploit marine resources, primarily materials located within oceans and other bodies of water. Historically, humans have used artificial underwater structures such as ships, oil rigs, boats, submarines, robots, and autonomous vehicles to harness marine resources, encompassing commercial and military applications. Whether static or dynamic, these underwater platforms rely on different propulsion systems for manoeuvrability, including nuclear power, diesel engines, fuel cell/air independent propulsion (AIP) and electrically driven motors. These propulsion systems create thrust, using propeller or water jet mechanisms to move inside waterbodies. This study traces the evolution of underwater propulsion motors in deep-sea applications from their inception to the current state-of-the-art advancements. It provides a detailed overview of existing underwater motor and controller technologies used for underwater platforms, emphasising their capabilities and limitations while highlighting potential areas for innovation in the design of multiphase motors. This paper critically evaluates the current electric propulsion motors used in underwater platforms. Furthermore, the paper identifies gaps in existing technologies for multiphase electric motors designed for deep-sea application, which are more than a hundred meters deep with power requirements exceeding 200 kW with the motor mounted externally, directly exposed to the high pressures of the deep-sea environment, setting the stage for future research and development opportunities that can lead to improved exploration of oceans and their resources.